Modification method of magnetically soft alloy and prepared wave-absorbing agent

By thermal oxidation treatment of Fe3Si alloy, a core-shell type Fe3Si@Fe2O3/Fe3Si wave absorber is formed, which solves the problems of narrow bandwidth and single loss mechanism of existing wave absorber materials, and realizes a wide-band and high-efficiency wave absorber, which is suitable for the needs of "thin, light, wide and strong".

CN119920610APending Publication Date: 2025-05-02NAVAL AVIATION UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510017448.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The effective absorption bandwidth of existing absorbing materials is narrow, with large surface density and a single loss mechanism, making it difficult to meet the needs of "thin, light, wide and strong".

Method used

The Fe3Si alloy is partially oxidized by thermal oxidation method to form a core-shell type Fe3Si@Fe2O3/Fe3Si wave absorber. The method includes ball milling to prepare a sheet-like Fe3Si alloy and thermal oxidation in an air atmosphere of 200°C for 2 hours to form a Fe2O3 shell and a dispersed Fe3Si grain.

Benefits of technology

It significantly improves the effective absorption bandwidth and absorption performance of the absorber, has a small matching thickness and low cost, is suitable for commercial applications, and enhances the absorption effect of electromagnetic waves through the interface loss mechanism.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920610A_ABST
    Figure CN119920610A_ABST
Patent Text Reader

Abstract

The invention relates to a modification method of a magnetically soft alloy and a prepared wave-absorbing agent, and belongs to the technical field of wave-absorbing agents. The invention relates to a modification method of a magnetically soft alloy, which comprises the following steps: (1) carrying out pretreatment and ball milling on a Fe3Si alloy to obtain a flaky Fe3Si alloy material; and (2) carrying out thermal oxidation modification treatment on the Fe3Si alloy material in the step (1) to obtain the core-shell type flaky ultra-wideband wave-absorbing agent material Fe3Si-coated Fe2O3 / Fe3Si. Compared with other ferromagnetic magnetic wave materials at present, the prepared Fe3Si-coated Fe2O3 / Fe3Si wave absorbing agent has the advantages that the effective absorption bandwidth is wide, the matching thickness is small, and the wave absorbing performance is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing agents, and in particular relates to a modification method of a soft magnetic alloy and a prepared wave absorbing agent. Background Art

[0002] Electromagnetic waves are a key part of modern innovative technologies and are widely used in communications, home appliances and other fields. However, this also brings about electromagnetic interference and radiation problems, as well as potential risks to human health. Therefore, it is particularly important to develop electromagnetic wave absorbing materials, which effectively slow down the reflection and penetration of electromagnetic waves by converting electromagnetic energy into heat or other forms of energy, thereby avoiding secondary electromagnetic pollution.

[0003] In order to meet the requirements of "thin, light, wide and strong", scholars have carried out a lot of work in the research and development of absorbing materials, mainly focusing on the research and development of new materials, as well as the influence of particle microstructure, morphology and surface coating on the electromagnetic properties of materials, aiming to find ways to obtain high magnetic permeability and controllable dielectric constant in the target band. Among them, ferromagnetic alloy materials have advantages such as high saturation magnetization intensity and adjustable magnetic permeability, providing a new technical approach for broadband absorption of microwave materials. However, since the magnetic properties of spherical materials are limited by the "Snoek limit" at high frequencies, it is difficult to meet the requirements of "thin, light, wide and strong", which limits its practical application in equipment; and the thickness of two-dimensional sheet materials is less than the skin depth, even in the case of low resistivity, high-frequency eddy currents will be suppressed, breaking the Snoek limit to obtain excellent high-frequency electromagnetic properties.

[0004] With the rapid development of electronic communication technology and the application of 5G communication technology, electromagnetic pollution and interference problems in human life have become increasingly serious, affecting human health and the efficient operation of equipment. The research and development of absorbing materials is one of the effective means to solve the above problems. For example, in the literature, Flaky FeSi particles with tunable size, morphology and microstructure developing for high-efficiency and broadband absorbing materials. [J]. Journal of Magnetism and Magnetic Materials, 2021, 527: 167800, FeSi flakes of different particle sizes were synthesized, and the FeSi@SiO2 obtained by hydrogen annealing and hydrothermal method had a minimum reflection loss (RL) of -73dB at 2.5GHz, a matching thickness of 3mm, and an effective absorption bandwidth (less than -5dB) of 13GHz when the matching thickness was 1mm. In the literature Enhancement of microwave absorption performance of FeSiCr magnetic powder by dielectric polarization modulation, Journal of Physics and Chemistry of Solids, 2024, 185, 111734, flaky FeSiCr magnetic powder was compounded with an organic metal skeleton (MIL-88(Fe)) and subjected to carbonization heat treatment. The obtained Fe3O4@C@FeSiCr composite material had an effective absorption bandwidth of 5.68 GHz (12.32-18 GHz) and a RL of -35.71 dB when the matching thickness was 1.08 mm. The FeCo@SiO2@C gradient composite material designed by hydrothermal method and vapor deposition technology in the literature Robust silicaand carbon bilayers decorating spherical FeCo alloys for high-performanceanti-corrosion microwave absorption[J]. Journal of Alloys and Compounds 936(2023) 168301. has a minimum reflection loss of -35.68dB at 9.25GHz and an effective bandwidth of 3.85GHz (7.33-11.18GHz).

[0005] The absorbing materials prepared in the above-mentioned literature show good absorbing performance, but still face problems such as narrow effective absorption bandwidth (less than -10dB), high surface density, and single loss mechanism.

[0006] The core-shell structure is an ordered assembly structure at the micro-nano scale formed by encapsulating another material through chemical bonds or other forces. This structure integrates the properties of the two materials inside and outside, and complements each other's deficiencies. It has been an important research direction in recent years on the determination of properties by structure. The core-shell structure has broad application prospects in catalysis, photocatalysis, batteries, gas storage and separation. In the field of microwave absorption, the coating structure can provide more possibilities for microwave absorption. For example, the interface effect between the core and the shell can be used to increase the interface loss during the microwave absorption / loss process; the presence of the shell layer can appropriately increase the microscopic size of the material, reduce the surface activation energy, and alleviate the agglomeration of nanomaterials; in addition, the functional shell layer can prevent the internal material from directly contacting the environmental medium, and can improve the corrosion resistance of the absorber.

[0007] Therefore, combining the flake structure with the core-shell structure, while breaking through the Snoke limit, enables the absorber to have the above characteristics, which is the main reason for obtaining excellent absorbing performance. Summary of the invention

[0008] In view of the problems of narrow effective absorption bandwidth, large surface density, and single loss mechanism of existing absorbing materials, the present invention provides a modification method of soft magnetic alloy and a prepared absorbing agent to solve the above problems. The present invention prepares an ultra-wideband, low surface density, and multi-loss mechanism coordinated Fe3Si@Fe2O3 / Fe3Si absorbing agent, and proposes a soft magnetic alloy thermal oxidation method with simple operation, short preparation cycle, and large-scale preparation. Combined with the thermogravimetric analysis results of the material, in an air atmosphere, thermal oxidation at 200°C for 2h, part of the Fe3Si is oxidized to Fe2O3, and fine Fe3Si grains are dispersed in the Fe2O3 shell layer, forming a Fe2O3 / Fe3Si composite coating layer. Compared with other current ferromagnetic magnetic wave materials, the Fe3Si@Fe2O3 / Fe3Si absorbing agent prepared by the present invention has a wide effective absorption bandwidth, a small matching thickness, and significantly improved absorbing performance.

[0009] In a first aspect, the present invention provides a method for modifying a soft magnetic alloy, comprising the following steps: (1) Pre-treating the Fe3Si alloy and ball milling to obtain a flaky Fe3Si alloy material; (2) The Fe3Si alloy material in step (1) is subjected to thermal oxidation modification treatment to obtain a core-shell type flaky ultra-wideband absorber material Fe3Si@Fe2O3 / Fe3Si. The partial oxidation of the Fe3Si alloy and the formation of surface Fe2O3 / Fe3Si can reduce the contact between the Fe3Si alloy and the environment and improve the weather resistance; the low conductivity Fe2O3 can improve the impedance matching of the absorber; the core-shell coating structure can increase the radar wave loss mechanism (interface loss mechanism) of the absorber.

[0010] Furthermore, the Fe3Si alloy is spherical and has a particle size of 300-500 μm.

[0011] Furthermore, during the mixing process in the ball mill, an inert gas is used for protection; the inert gas can be argon.

[0012] Furthermore, in step (1), the dry ball milling is carried out by placing the materials into a ball milling jar at a ball-to-powder ratio of 10:1 and ball milling is carried out for 24 hours, with a 15-minute break after every hour of ball milling.

[0013] Furthermore, in step (2), the alloy is heated and oxidized in a tubular furnace, and air is introduced to provide an oxygen source; the oxidation temperature is 200° C., and the oxidation time is 2 hours.

[0014] Furthermore, the heating rate of the tube furnace was 5°C / min.

[0015] In a second aspect, the present invention provides a Fe3Si@Fe2O3 / Fe3Si absorber prepared by the above method. The absorber has a core-shell structure, and Fe3Si grains are dispersed in Fe2O3.

[0016] The beneficial effects of the present invention are: (1) Compared with other ferromagnetic magnetic wave materials currently available, the Fe3Si@Fe2O3 / Fe3Si absorber prepared by the present invention has a wide effective absorption bandwidth, a small matching thickness, and significantly improved absorption performance.

[0017] (2) The raw materials of the Fe3Si@Fe2O3 / Fe3Si absorber prepared by the present invention are simple and easy to obtain, low in cost, and can meet the requirements of commercial applications.

[0018] (3) The oxidant used in the thermal oxidation treatment of the present invention is air, which is relatively low in cost; the oxidation temperature is 200°C, which is a low-temperature oxidation environment; the oxidation time is short, which effectively saves costs.

[0019] (4) In the Fe3Si@Fe2O3 / Fe3Si absorber prepared by the present invention, Fe3Si grains are dispersed in the Fe2O3 shell layer, which increases the interface loss while avoiding sacrificing the magnetism of the shell layer, thereby reducing the magnetic loss performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 It is the XRD diagram of the Fe3Si micron sheet prepared in step (2) of Example 1, the Fe3Si-2 prepared in step (3) and the Fe3Si-4 prepared in Comparative Example 1.

[0022] Figure 2 These are SEM images of the Fe3Si micron sheets prepared in step (2) of Example 1, the Fe3Si-2 prepared in step (3), and the Fe3Si-4 prepared in Comparative Example 1. Figure 2 (A1), (A2) and (A3) are SEM images of Fe3Si microsheets; (B1), (B2) and (B3) are SEM images of Fe3Si-2; (C1), (C2) and (C3) are SEM images of Fe3Si-4.

[0023] Figure 3 TEM images of the Fe3Si micron sheets prepared in step (2) of Example 1, the Fe3Si-2 prepared in step (3), and the Fe3Si-4 prepared in the comparative example. Figure 3 (a), (b) and (c) are TEM images of Fe3Si-2; (d) is the HAADF image of Fe3Si-2; (d1), (d2) and (d3) are element mapping images of Si, O and Fe elements, respectively.

[0024] Figure 4 This is the XPS graph of Fe3Si-2 prepared in Example 1.

[0025] Figure 5 1 is a hysteresis loop diagram of the Fe3Si micron sheet prepared in step (2) of Example 1, the Fe3Si-2 prepared in step (3), and the Fe3Si-4 prepared in the comparative example.

[0026] Figure 6 The reflection loss diagrams are of the Fe3Si micron sheet prepared in step (2) of Example 1, the Fe3Si-2 prepared in step (3), and the Fe3Si-4 prepared in the comparative example. In the figure, (a) is Fe3Si-4; (b) is Fe3Si-2; (c) is Fe3Si micron sheet. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0028] Example 1 A method for preparing a Fe3Si@Fe2O3 / Fe3Si absorber, comprising the following steps: (1) Spherical iron-silicon alloy Fe3Si was purchased and had a particle size of 300-500 μm.

[0029] (2) The Fe3Si alloy obtained in step (1) and stainless steel balls were placed in a ball mill at a ball-to-powder ratio of 10:1, and ball milled under argon protection for 24 hours, wherein the ball mill rotated forward for 1 hour and then stopped for 15 minutes to obtain Fe3Si micron flakes.

[0030] (3) Weigh an appropriate amount of the flaky Fe3Si alloy obtained in step (2) and place it in a porcelain boat. Place the porcelain boat with the sample in a tube furnace, and then place insulation materials at both ends of the quartz tube. Set the tube furnace program as follows: heating rate 5°C / min, from room temperature to 200°C; keep warm for 2 hours. Start the tube furnace and perform heating oxidation. When the test is completed, the tube furnace automatically cools to room temperature, and the test sample is taken out to obtain the Fe3Si@Fe2O3 / Fe3Si absorber (Fe3Si-2).

[0031] Comparative Example 1 A method for preparing a Fe3Si@Fe2O3 absorber, the steps are as follows: (1) Spherical iron-silicon alloy Fe3Si was purchased and had a particle size of 300-500 μm.

[0032] (2) The Fe3Si alloy obtained in step (1) and stainless steel balls were placed in a ball mill at a ball-to-powder ratio of 10:1, and ball milled under argon protection for 24 hours, wherein the ball mill rotated forward for 1 hour and then stopped for 15 minutes to obtain Fe3Si micron flakes.

[0033] (3) Weigh an appropriate amount of the flaky Fe3Si alloy obtained in step (2) and place it in a porcelain boat. Place the porcelain boat with the sample in a tube furnace, and then place insulation materials at both ends of the quartz tube. Set the tube furnace program as follows: heating rate 5°C / min, from room temperature to 200°C; keep warm for 4 hours. Start the tube furnace and perform heating oxidation. When the test is completed, the tube furnace automatically cools to room temperature, and the test sample is taken out to obtain the Fe3Si@Fe2O3 / Fe3Si absorber (Fe3Si-4).

[0034] Test Case The Fe3Si@Fe2O3 / Fe3Si absorber (Fe3Si-2) prepared in Example 1, the Fe3Si@Fe2O3 / Fe3Si absorber (Fe3Si-4) prepared in Comparative Example 1 and the raw material spherical iron-silicon alloy Fe3Si used in Example 1 were subjected to relevant tests, including XRD, SEM, TEM, XPS, hysteresis loop of the sample and reflection loss of the sample. The specific results are as follows: Figure 1 to Figure 6 shown.

[0035] Figure 1 The XRD patterns of Fe3Si microsheets prepared in step (2) of Example 1, Fe3Si-2 prepared in step (3), and Fe3Si-4 prepared in the comparative example. The Fe3Si alloy was ball milled, and Fe3Si-2 and Fe3Si-4 were thermally oxidized for 2 h and 4 h, respectively. In the XRD spectrum of Fe3Si alloy, the three peaks at 2θ=35°, 65° and 82° correspond to the (220), (400) and (422) crystal planes of Fe3Si (JPDS) alloy, respectively, indicating that ball milling does not affect its phase composition; after 2h of thermal oxidation, the intensity of the diffraction peak corresponding to Fe3Si-2 alloy decreases, the peaks at 65° and 82° almost disappear, and a weak peak appears at 35.8°; when the thermal oxidation time is 4h, the intensity of the diffraction peak corresponding to Fe3Si-4 further decreases, and new diffraction peaks appear at 2θ=33.2°, 35.8° and 62.6°, corresponding to the (104), (110) and (214) crystal planes of α-Fe2O3, respectively, indicating that 2θ=35.8° in Fe3Si-2 sample corresponds to the (110) crystal plane of α-Fe2O3, and part of the Fe3Si phase is transformed into the Fe2O3 phase after thermal oxidation treatment.

[0036] Figure 2 SEM images of the Fe3Si micron sheets prepared in step (2) of Example 1, the Fe3Si-2 prepared in step (3), and the Fe3Si-4 prepared in the comparative example. Figure 2A1~A3 are Fe3Si alloys that have not been thermally oxidized. After ball milling for 24 hours, the morphology is a typical flake material with a diameter between 150~240nm. After thermal oxidation at 200℃ for 2h, the flake morphology of the Fe3Si-2 sample did not change, and the sample surface became smooth. This is due to the elimination of surface impurities and the formation of oxides during the thermal oxidation process. In addition, stacking phenomenon also occurs on the surface, which can increase the contact area after microwaves enter the material. After 4 hours of thermal oxidation, the Fe3Si-4 sample showed obvious agglomeration.

[0037] Figure 3 TEM images of the Fe3Si micron sheets prepared in step (2) of Example 1, the Fe3Si-2 prepared in step (3), and the Fe3Si-4 prepared in the comparative example.

[0038] Figure 3 (a), (b) and (c) are TEM images of Fe3Si-2; (d) is the HAADF image of Fe3Si-2; (d1), (d2) and (d3) are elemental mapping images of Si, O and Fe elements respectively. Obvious coating phenomenon can be seen from (a) and (b), and fine dispersed grains are observed in the coating layer. In high-magnification TEM, the interplanar spacing of the grains distributed therein is 0.201nm through Fourier transform measurement, corresponding to the (220) crystal plane of the Fe3Si phase. Combined with the XRD results, it can be seen that after 2 hours of thermal oxidation treatment, the outer coating layer is α-Fe2O3 phase, and Fe3Si phase grains are dispersed in it. In the EDS surface scan, the distribution of elements further shows that the outer part of Fe3Si is oxidized.

[0039] Figure 4 The XPS graph of Fe3Si-2 after thermal oxidation for 2 hours. (a) The full spectrum shows the presence of Fe, Si and O elements in the sample. (b) The Si 2p spectrum, 101.3eV corresponds to the Si-O bond, indicating that part of the Si in the sample is oxidized. (c) The Fe 2p spectrum, where the characteristic peaks at 710.1eV and 723.6eV correspond to Fe o 3+ 2p 3 / 2 and Fe o 3+ 2p 1 / 2 , the characteristic peaks at 718.1eV and 732.5eV correspond to Fe t 3+ 2p 3 / 2 and Fe t 3+ 2p 1 / 2This indicates the presence of +3-valent iron in the sample. In addition, the two peaks at 718.1eV and 732.5eV correspond to the satellite peaks of Fe2O3, further indicating that part of the surface Fe3Si is oxidized to Fe2O3 shell. In (d), the two characteristic peaks at 529.3eV and 530.8eV correspond to Fe-O and Si-O bonds, respectively, further verifying the fact that the sample surface is oxidized.

[0040] from Figure 5 It can be seen from the hysteresis loop that the saturation magnetization intensity ( Ms ) is 66.1emu / g, and the coercivity is 373.2Oe; the Ms values ​​of Fe3Si-2 and Fe3Si-4 after 2h and 4h of thermal oxidation are 89.5 and 115.4emu / g, respectively, and the coercivity decreases to 353.2Oe and 322.4Oe, respectively. The above numerical changes indicate that the saturation magnetization of the material is not affected by the thermal oxidation treatment, which is due to the dispersed Fe3Si in the coating layer; in addition, the decrease in the coercivity value is due to the increase in the oxide content as the thermal oxidation time increases.

[0041] from Figure 6 It can be seen from the reflection loss curve that when the matching thickness is 1.8mm, the effective bandwidth (less than -10dB) of the Fe3Si alloy that has not been thermally oxidized is 5.5GHz, and the minimum reflection loss is -19.9dB; the effective bandwidths of Fe3Si-2 and Fe3Si-4 that have been thermally oxidized are 8.0GHz and 3.1GHz, respectively, and the minimum reflection losses are -40.6dB and -11.8dB, respectively. The above analysis shows that after proper heat treatment, a Fe2O3 coating layer is generated on the surface of Fe3Si, which enhances the impedance matching ability of the material. At the same time, the dispersed Fe3Si grains in the coating layer take into account the magnetic loss ability of the material.

[0042] Will Figure 6 The values ​​obtained from the reflection loss curve are compared with the relevant test data of the prepared absorbing materials in the existing literature, as shown in Table 1.

[0043] Table 1 - Test results

[0044] Note: The reference list is as follows: [1] Magnetic and electromagnetic properties of Fe3O4 / Fe compositesprepared by a simple one-step ball-milling. Journal of Alloys and Compounds708 (2017) 587-593. [2] Enhancement of microwave absorption performance of FeSiCrmagnetic powder by dielectric polarization modulation[J]. Journal of Physicsand Chemistry of Solids 185 (2024) 111734. [3] Flaky FeSi particles with tunable size, morphology andmicrostructure developing for high-efficiency and broadband absorbingmaterials[J]. Journal of Magnetism and Magnetic Materials, 2021, 527:167800. [4] Electromagnetic wave absorption properties of core double-shellstructured α-Fe(Si)@Fe3O4@SiO2composites[J]. Applied Surface Science 615(2023) 156345. [5] Fe3Si-core / amorphous-C-shell nanocapsules with enhanced microwaveabsorption, J. Magn. Magn. Mater. 471 (2019) 561–567. [6] Magnetic behavior, electromagnetic multiresonances, and microwaveabsorption of the interfacial engineered Fe@FeSi / SiO2nanocomposite, ACS Appl.Nano Mater. 1 (2018) 1309–1320. By comparing and analyzing the results in Table 1, it is found that the effective bandwidth (8 GHz) of the Fe3Si-2 absorber obtained in this case is significantly higher than that of existing absorbers, and the matching thickness is thinner. This is because (1) the dispersed distribution of magnetic FeSi grains in the coating layer avoids the sacrifice of magnetic loss of the absorber, and the Fe2O3 with lower conductivity in the coating layer improves the matching performance of the absorber, which is conducive to more electromagnetic waves entering the material; (2) the core-shell coating structure provides an interface loss mechanism, and the magnetic loss coupling effect with Fe3Si is conducive to the rapid attenuation of electromagnetic waves, increasing the overall absorption performance of Fe3Si-2. The above reasons enable the Fe3Si-2 absorber invented in this case to show a wider effective absorption bandwidth and reflection loss performance under the condition of a smaller matching thickness.

[0045] Although the present invention has been described in detail by referring to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person skilled in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, and they shall be within the scope of protection of the present invention.

Claims

1. A method for modifying a soft magnetic alloy, characterized in that: The following steps are involved: (1) Pre-treating the Fe3Si alloy and ball milling to obtain a flaky Fe3Si alloy material; (2) The Fe3Si alloy material in step (1) is subjected to thermal oxidation modification treatment to obtain a core-shell type sheet-like ultra-wideband absorber material Fe3Si@Fe2O3 / Fe3Si.

2. The method for modifying a soft magnetic alloy according to claim 1, characterized in that: The Fe3Si alloy is spherical with a particle size of 300~500 μm.

3. A method for modifying a soft magnetic alloy as claimed in claim 1, characterized in that: During the ball milling process, an inert gas was used for protection.

4. A method for modifying a soft magnetic alloy as claimed in claim 3, characterized in that: The inert gas is argon.

5. A method for modifying a soft magnetic alloy as claimed in claim 1, characterized in that: In step (1), the ball mill is placed in a ball milling jar at a ball-to-powder ratio of 10:1 and ball milled for 24 hours; wherein the ball milling is stopped for 15 minutes after every hour of ball milling.

6. A method for modifying a soft magnetic alloy as claimed in claim 1, characterized in that: In step (2), the alloy is heated and oxidized in a tubular furnace, and air is introduced to provide an oxygen source; the oxidation temperature is 200° C., and the oxidation time is 2 hours.

7. A method for modifying a soft magnetic alloy as claimed in claim 6, characterized in that: The heating rate of the tube furnace was 5 °C / min.

8. A Fe3Si@Fe2O3 / Fe3Si absorber obtained by the modification method as claimed in claim 1.